Conhecimento dos trabalhadores de uma empresa de manutenção industrial em relação à proteção auditiva - Greca, Ana Ligia Melo Martins (2010)
Objective. Evaluate the knowledge of workers exposed to noise in relation to hearing protection and identify prevalence and outbreaks of noiseinduced hearing loss over three years. Method. The sample consisted of 65 workers at an engineering company aged 21 to 57 years, all male and exposed to noise at or above 85 dB (A). All workers wore hearing protection. The procedures included the use of the questionnaire "Beliefs and attitudes about hearing protection and hearing loss" and analysis of audiometric tests performed in 2007, 2008 and 2009. Results: Most workers (70.8%) had a time of noise exposure in the company within one to five years. Of the total, 33 workers (50.7%) reported complaints regarding the use of hearing protectors. The most frequent complaints were itching (23.1%) and difficulty in communication (12.3%). Most workers (78.5%) reported working in noisy environment. The prevalence of noise-induced hearing loss ranged from 21.6% to 38.5% during the three years. The onset of hearing loss ranged from 23 to 38.5% in the comparison of tests from 2007 to 2009. The questionnaire answers indicated, in most cases, workers attached importance to the hearing and know the strategies of hearing protection. Conclusion: There was a statistically significant association between age and hearing loss. The questionnaire results indicated that, in general, workers have knowledge about hearing protection, despite the high prevalence rate and triggering noise-induced hearing loss